Strategi Promosi Pre-Order Buku melalui Instagram: Analisis Model SOSTAC pada Penerbit Bukune - Aisy Andini Savitri; Suparman Suparman (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study analyzes how Bukune Publisher optimizes Instagram as a strategic channel for book pre-order promotion by applying the SOSTAC planning model. The growing reliance on social media as a primary source of reading recommendations and the intensifying competition among publishers in the digital ecosystem make structured promotional planning increasingly important, especially in the pre-order phase when readers decide to purchase before the physical book is available. The research aims to describe and explain the stages of Situation, Objectives, Strategy, Tactics, Action, and Control in Bukune’s Instagram-based promotion. This study uses a qualitative descriptive approach with a case study design. Data were collected through semi-structured interviews with the Social Media Specialist, marketing promotion staff, editor, and readers who follow Bukune’s Instagram account, as well as content observation on @bukune. The findings show that Bukune maps the initial condition of the account and author profiles, formulates emotional and sales objectives differentiated by author category, designs internal segmentation and positioning strategies, and translates them into a mix of Instagram formats and features supported by cross-functional coordination. The study implies that the SOSTAC model provides a useful framework for publishers to develop more structured, adaptive, and audience-oriented pre-order promotion strategies in digital book marketing